Occupational Health and Safety at Workplace: A Reflective Review of Nepal’s TVET Sector - Rana, Chandu (Journal of Technical and Vocational Education and Training, 2026)
Ensuring occupational health and safety (OHS) is essential for maintaining a secure and healthy work environment. It encompasses multiple aspects, such as occupational health and safety-related training and awareness among the formal and informal workers, integration of hands-on practical practices in Technical and Vocational Education and Training (TVET), and proper use of occupation-wise Personal Protective Equipment (PPE) at workplace. Although it is one of the major components of decent work, Nepal still has limited access to occupational health and safety along with the use of PPE at workplace. This review paper was prepared through relevant literature review and searches on Google Scholar to access a diverse range of articles, research papers and reports. The findings reveal significant gaps in OHS awareness, training and practical implementation, particularly in the TVET sector. Despite increasing emphasis on employee skills development, workplace safety remains inadequately addressed. Insufficient infrastructures, lack of occupation-specific PPE, limited OHS hands-on practical processes in training curricula and the absence of structured monitoring systems contribute to unsafe working conditions and unprepared workers in Nepal. The study emphasizes the need to integrate practical OHS practices into TVET curricula, engage certified OHS experts, improve the quality and accessibility of PPE, and raise awareness among workers, employers and government entities. These measures, combined with an effective enforcement of safety regulations, are essential for fostering a safe work environment, enhancing workers' well-being and promoting sustainable economic growth.